2009
DOI: 10.1007/s00535-009-0065-3
|View full text |Cite
|
Sign up to set email alerts
|

The use of indigocarmine spray increases the colonoscopic detection rate of adenomas

Abstract: Chromocolonoscopy increases the detection of neoplastic polyps and flat adenomas, particularly diminutive polyps, but does not increase the detection of advanced lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…The benefit conferred by PCC in average-risk populations is a matter of controversy, however. While one study found increased overall adenoma detection rates,14 other studies have reported that indigo carmine spraying detects significantly more diminutive and flat colorectal adenomas, but without a statistically significant overall increase in total adenoma detection rates or more frequent identification of patients with at least one adenoma 15 17–19. However, in three of these studies,15 17 18 the sample sizes were not calculated in such a way as to be capable of detecting differences <25%, and the patient numbers were limited to <300.…”
Section: Discussionmentioning
confidence: 93%
“…The benefit conferred by PCC in average-risk populations is a matter of controversy, however. While one study found increased overall adenoma detection rates,14 other studies have reported that indigo carmine spraying detects significantly more diminutive and flat colorectal adenomas, but without a statistically significant overall increase in total adenoma detection rates or more frequent identification of patients with at least one adenoma 15 17–19. However, in three of these studies,15 17 18 the sample sizes were not calculated in such a way as to be capable of detecting differences <25%, and the patient numbers were limited to <300.…”
Section: Discussionmentioning
confidence: 93%
“…A recent Cochrane review [12] analysed four such trials [13][14][15][16], excluding any screening programmes for inflammatory bowel surveillance or polyposis syndromes, and found a significant difference in favour of chromoendoscopy for all detection outcomes and in particular, in identifying patients with at least one and patients with three or more neoplastic lesions. A further recent study by Togashi et al [17] compared chromoendoscopy vs conventional colonoscopy and found that chromoendoscopy detected more neoplastic polyps, especially small (< 5 mm) and flat polyps, but did not increase the detection of advanced lesions.…”
Section: Aims Of Chromoendoscopymentioning
confidence: 98%
“…A further recent study by Togashi et al. [17] compared chromoendoscopy vs conventional colonoscopy and found that chromoendoscopy detected more neoplastic polyps, especially small (< 5 mm) and flat polyps, but did not increase the detection of advanced lesions.…”
Section: Chromoendoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…They found polyp detection rates to be greater using contrast in particular subsets of cases [31,32]. There is slight controversy regarding the significance of the additional yield of chromoendoscopy with dye spray, as the main advantages seem to be in detecting diminutive polyps [33], although right-sided adenomas and polyps with a certain morphology also seemed to be detected significantly more often in other studies [34]. The case for using digital contrast in lesion detection is weaker, with initial studies reporting an increased yield but later work suggesting there may be a learning effect that depends on other operator factors rather than the digital contrast enhancement itself [35].…”
Section: Use Of Contrast Enhancement Techniquesmentioning
confidence: 99%